Digital Sor-Singgih: A Narrative Inquiry into Ethnotech-Pragmatics among Youth in Denpasar - Wedananta, Kadek Adyatna; Budiarta, I Komang (Journal of Language and Literature Studies, 2026)
The‍‌ research broadens the Ethnotech-Pragmatics conceptual model, initially introduced by Wedananta (2023), for investigating how the young people of Denpasar juggle the tensions between Balinese cultural values and the digital world of Instagram. This‍‌‍‍‌‍‌‍‍‌ paper employs a narrative qualitative method so as to reveal the "genuine experience" of these young people in their engagement with Balinese cultural values and the digital world of Instagram, which is a follow-up to the research that initially uncovered this ‍‌‍‍‌‍‌‍‍‌phenomenon. This study was done by first having ten high school students, aged 17-18 of Denpasar talk separately and at length, and then it showed how the technical features of digital communication - such as the 'Close Friends' list, temporary Stories, and sticker use - can be the means to go around traditional Sor-Singgih (language hierarchy) and tactic of keeping one's face or dignity. Data‍‌ collection was done through semi-structured narrative interviews as well as "scroll-back" sessions where participants performed some phone interactions and narrated the context. Then, thematic narrative analysis was employed to examine the data. The findings present that Ethnotech-Pragmatics is more than a language change; it is also a profound identity negotiation in which technology acts as a facilitator of politeness across different cultures. Moreover, the introduction of ethnotech-pragmatics in the school curriculum offers a valuable opportunity for the youth of Bali to reconnect with their cultural heritage on a profound ‍‌‍‍‌‍‌‍‍‌level.